2005
DOI: 10.1001/jama.293.10.1197
|View full text |Cite
|
Sign up to set email alerts
|

Role of Computerized Physician Order Entry Systems in Facilitating Medication Errors

Abstract: DVERSE DRUG EVENTS (ADES) are estimated to injure or kill more than 770 000 people in hospitals annually. 1 Prescribing errors are the most frequent source. 2-5 Computerized physician order entry (CPOE) systems are widely viewed as crucial for reducing prescribing errors 2,3,6-17 and saving hundreds of billions in annual costs. 18,19 Computerized physician order entry system advocates include researchers, clinicians, hospital administrators, pharmacists, business councils, the Institute of Medicine, state legi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
880
4
20

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,726 publications
(920 citation statements)
references
References 39 publications
16
880
4
20
Order By: Relevance
“…A simple majority (159, 68.2%) utilized the Internet daily while a higher portion (171, 73.4%) possess email address and nearly onefifth (22,19.8%) of the participants came from facilities with full computerization of processes. The most frequently suggested solution or action (107, 60.8) to be taken on paper records in the wake of HIT is to archive them and this was distantly followed by electronic back up (30, 17.0%).…”
Section: Attitude Toward Health Information Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…A simple majority (159, 68.2%) utilized the Internet daily while a higher portion (171, 73.4%) possess email address and nearly onefifth (22,19.8%) of the participants came from facilities with full computerization of processes. The most frequently suggested solution or action (107, 60.8) to be taken on paper records in the wake of HIT is to archive them and this was distantly followed by electronic back up (30, 17.0%).…”
Section: Attitude Toward Health Information Technologymentioning
confidence: 99%
“…For instance, studies have shown that its implementations could not go without significant risks to patients and providers [16]. Cases of fatal insulin overdose as a result of mix-up in the bar-coded wristbands [17], dehumanization as providers focused computer screens in lieu of their critically ill-patients [18], incorrect medications chosen from computerized pick lists [19], and most awful, escalation of paediatric mortality subsequent to computerized system [18]. Furthermore, researchers have reported that sites where CPOE were implemented still experience high rates of medication errors and adverse drug events (ADEs) [20], errors related to entry, retrieval, communication and coordination of health information [21] and low adoption rate of HIT [22].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics of nurses' experience: During the period of implementation, nurses' attitude and satisfaction increased overtime as they experienced more with the system (Ammenwerth et al, 2011;Carayon et al, 2011;Lee et al, 2008). Fidelity HIS functionality did not meet the nurses' needs nor support their workflows and practice (Novak et al, 2013;Stevenson et al, 2010); workflow interruptions, additional work (Eley et al, 2009;Lee et al, 2008), unintended consequences (Dowding et al, 2009;Koppel et al, 2005). A particular HIS may fit one context but not others (Ackerman et al, 2012;Gough et al, 2014;Jeskey et al, 2011) Firstly, in regard to usability, Stevenson et al (2010) reviewed five empirical studies published from 2000 to 2009 and reported on nurses' experiences with HIS systems.…”
Section: Usefulness / Effectivenessmentioning
confidence: 99%
“…According to their review, HIS functionality was not useful nor did it meet the nurses' needs nor support their workflow; the user-interfaces were found to be difficult to use and navigate. Overriding of the system, duplication of documentation, and a reversion to familiar systems such as paper recording were reported as major work-around strategies when technology solutions did not meet clinicians' needs (Dowding et al, 2009;Koppel et al, 2005). More recently, Mills et al (2013) reviewed 21 studies published between 1995 and 2010 which took place in acute care contexts in Australia and New Zealand.…”
Section: Usefulness / Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation